INTEGRATING SOCIOCULTURAL CONTEXTS IN SCIENCE EDUCATION: COMPARATIVE ANALYSIS AND STRATEGIC ADAPTATIONS - Moldalieva, Salamat; Baruti, Shukrije; Baruti-Sylejmani, Miranda; Koichubaeva, Nazira (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
The relevance of this study lies in its exploration of effective learning strategies across diverse sociocultural contexts, thereby underscoring the necessity to adapt educational practices in order to meet the requirements of culturally and socially varied student populations. The aim of this study was to investigate the impact of sociocultural factors on education in Kosovo and Kyrgyzstan, with a view to identifying effective adaptations of educational strategies within these unique cultural and historical settings. The applied research methods included a comparative analysis of the educational systems in Kosovo and Kyrgyzstan, and an interdisciplinary approach to examine the manner in which historical, cultural, and social factors are integrated into teaching methodologies. The results indicated that sociocultural contexts exert a significant influence on educational outcomes, thereby underscoring the necessity for tailored teaching strategies that take into account students' cultural backgrounds, social status, and ethical values. The study concluded that the successful adaptation of educational strategies requires comprehensive training for teachers, the incorporation of ethical considerations, and the development of culturally competent teaching materials. The present study offers profound insights into contemporary challenges, including technological integration and the need for diverse approaches. This study does a comparative examination of the sociocultural effects on education in Kosovo and Kyrgyzstan, providing insights into the influence of historical legacies and cultural variety on contemporary educational issues in both multicultural contexts. The findings provide recommendations for establishing inclusive educational environments, enhancing cultural competency among instructors, and utilising technology to meet the varied needs of students.